Controlled impacts for structure formation and properties of cement concretes - Yu. G. Ivaschenko; R. T. Mameshov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The paper considers controlled effects on changes in the properties of components and the control effect of technological methods and techniques for obtaining composite building materials with a set of specified properties.Method. Methods of mechano-physical, physicochemical, nanotechnological influence were applied.Result. The system-structural approaches are systematized and generalized by control actions at the stage of structure formation, technological stages, formation of the optimal structure and properties of cement concrete. The physicochemical principles and mechanisms of structure formation are given, based on establishing the role of controlling the mechano-physical, physico-chemical, nanotechnological methods of influencing the cement-water system. The possibility of controlling structural transformations in binder systems, including through the use of technological influences, has been revealed.Conclusion. The implementation of the impacts on the components of cement concretes will ensure the targeted design of the structures of modern building materials.